Comparison of Dawah Models on Facebook: Wahdah Islamiyah and S. Ahmad Fadl Al-MahdalyComparison of Dawah Models on Facebook: Wahdah Islamiyah and S. Ahmad Fadl Al-Mahdaly - Ismail, Nur Salim; Arifuddin, Arifuddin (Jurnal Mercusuar, 2021)
This article uses a qualitative-descriptive method by comparing the da'wah activities carried out by Wahdah Islamiyah Mamuju and S. Ahmad Fadl Al Mahdaly on Facebook. The sources used were direct observations of their accounts and evaluating their respective strengths and weaknesses. The option to use Facebook as a medium for da'wah is crucial due to the presence of digital media with convergent and fluid specifications, making it fertile ground for post-truth development. Society is flooded with public opinions influenced by emotions and personal beliefs, false information and factual distortions easily seep in when they align with our feelings and thoughts, while objective factual truth is sidelined. False news and hoaxes package lies, slander, and falsehood and spread rapidly with the help of buzzers from public figures, artists, or people who share similar beliefs and ideologies.